2015
DOI: 10.5740/jaoacint.14-261
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Nitrofuran Metabolites and Chloramphenicol in Shrimp with a Single Extraction and LC-MS/MS Analysis

Abstract: A method has been developed to quantify the nitrofuran metabolites 3-amino-5-morphorinomethyl-1,3-oxazolidinone, 3-amino-oxazolidinone, 1-aminohydantoin, and semicarbazide, as well as chloramphenicol in shrimp with a single extraction procedure followed by LC-MS/MS analysis. Dynamic selected reaction monitoring with positive and negative ionization mode switching was used. The method LODs were 0.5 ng/g for the nitrofuran metabolites and 0.3 ng/g for chloramphenicol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Several methods describe the assessment of nitrofuran metabolite concentrations in substances, including gas chromatography (Negrin, Valdes, Pouron, Lopez, & Borges, 2013;Petz, 1985), high performance liquid chromatography (Fernando, Munasinghe, Gunasena, & Abeynayake, 2017;Li, Ren, et al, 2018;Sniegocki, Giergiel, Sell, & Posyniak, 2018;Wilasinee, Sutthivaiyakit, & Sutthivaiyakit, 2015), and liquid chromatography tandem mass spectrometry (Du et al, 2014;El-Demerdash, Song, Reel, Hillegas, & Smith, 2015;Palaniyappan et al, 2013). Similarly, few studies have reported NFS determination using high-performance liquid chromatography and/or liquid chromatography tandem mass spectrometry (Horie et al, 1991;Segawa & Ikeda, 2000;Tao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods describe the assessment of nitrofuran metabolite concentrations in substances, including gas chromatography (Negrin, Valdes, Pouron, Lopez, & Borges, 2013;Petz, 1985), high performance liquid chromatography (Fernando, Munasinghe, Gunasena, & Abeynayake, 2017;Li, Ren, et al, 2018;Sniegocki, Giergiel, Sell, & Posyniak, 2018;Wilasinee, Sutthivaiyakit, & Sutthivaiyakit, 2015), and liquid chromatography tandem mass spectrometry (Du et al, 2014;El-Demerdash, Song, Reel, Hillegas, & Smith, 2015;Palaniyappan et al, 2013). Similarly, few studies have reported NFS determination using high-performance liquid chromatography and/or liquid chromatography tandem mass spectrometry (Horie et al, 1991;Segawa & Ikeda, 2000;Tao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Загалом, значення вмісту залишків хлорамфеніколу у пробах свинини, яловичини та м'яса птиці становили 0,0004-0,420 мкг/кг (CCβ становить 0,18 мкг/кг), яєць -0,001-0,017 мкг/кг (CCβ становить 0,18 мкг/кг), молока -0,004-0,101 мкг/кг (CCβ становить 0,15 мкг/кг), меду -0,002-0,029 мкг/кг (CCβ становить 0,15 мкг/кг). Використання хлорамфеніколу для лікування продуктивних тварин заборонено, оскільки наявність його залишків у продуктах харчування може провокувати тяжкі захворювання кровотворної системи в людей з підвищеною чутливістю до цього антибіотику [10][11][12][13][14]. До переліку показників, які підлягають обов'язковому контролю, відносяться антибіотики групи нітрофуранице синтетичні антибіотики, що швидко метаболізують.…”
Section: результати аналізу даних щодо перевищення концентрації антибunclassified
“…Nitrofuran (NF), mainly including furazolidone (FZD), nitrofurazone (NFZ), nitrofurantoin (NFT), and furaltadone (FTD), 1 are a class of synthetic broad-spectrum antibacterial drugs with a 5-nitro structure that were commonly used in veterinary drugs for the treatment of protozoan and gastrointestinal infections. 2 , 3 These drugs metabolize rapidly within a few hours after ingestion, and the residual metabolites could remain in the body for weeks, possibly even months, as protein-bound compounds. 4 6 These NF metabolite compounds have been proven to pose potential risk to human health because of their carcinogenic, teratogenic, and mutagenic potency.…”
Section: Introductionmentioning
confidence: 99%